Dispersion and domestication shaped the genome of bread wheat. Issue 5 (24th January 2013) - Berkman, Paul J.; Visendi, Paul; Lee, Hong C.; Stiller, Jiri; Manoli, Sahana; Lorenc, Michał T.; Lai, Kaitao; Batley, Jacqueline; Fleury, Delphine; Šimková, Hana; Kubaláková, Marie; Weining, Song; et al.
<x xml:space="preserve">Abstract</x> Summary Despite the international significance of wheat, its large and complex genome hinders genome sequencing efforts. To assess the impact of selection on this genome, we have assembled genomic regions representing genes for chromosomes 7A, 7B and 7D. We demonstrate that the dispersion of wheat to new environments has shaped the modern wheat genome. Most genes are conserved between the three homoeologous chromosomes. We found differential gene loss that supports current theories on the evolution of wheat, with greater loss observed in the A and B genomes compared with the D. Analysis of intervarietal polymorphisms identified fewer polymorphisms in the D genome, supporting the hypothesis of early gene flow between the tetraploid and hexaploid. The enrichment for genes on the D genome that confer environmental adaptation may be associated with dispersion following wheat domestication. Our results demonstrate the value of applying next‐generation sequencing technologies to assemble gene‐rich regions of complex genomes and investigate polyploid genome evolution. We anticipate the genome‐wide application of this reduced‐complexity syntenic assembly approach will accelerate crop improvement efforts not only in wheat, but also in other polyploid crops of significance.